Deposition of antimony on wafer by using sputtering system - Kam, Shu Xia (2019)
Antimony thin film is first deposited on the substrate by using the newly set-up sputtering system in Nanoelectronics Lab 1 (NEL1) through sputter deposition process. A thorough study on the newly set-up sputtering system has been done. By varying the deposition duration, we can manipulate the thickness of the thin film deposited on the substrate. By varying the substrate temperature and power used for sputtering will also change the properties of the thin film. Raman spectroscopy is used to determine the structure and property of thin film deposited on the substrate while AFM is used to determine the surface morphology and thickness of the thin film formed. A field effect transistor (FET) device is fabricated based on the thin film and an electrical testing is carried out to investigate the device characteristic of the thin film.